Hormonal and Psycho-Emotional Disorders in Women with Psychogenic Amenorrhea - Goncharenko, Vadym N. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The pathogenetic aspects of stress on reproductive health and fertility of a woman are multi-vector, this is justified by the need for timely diagnosis and the development of new approaches to differentiated treatment of PA. Objective: to determine the characteristics of the hormonal profile, the psycho-emotional state and changes in the bioelectric activity of the brain in women with stress-induced psychogenic amenorrhea (PA). Material and Methods: The main group included 54 women with PA from 19 to 37 years, the control group – 25 healthy women from 18 to 35 years. Blood plasma FSH, LH, E2, P, Pr, DHEAS, C levels were checked by the immuno-enzymatic method, bioelectric activity measurement of the brain – with an electroencephalography, women psycho-emotional status – by the Spielberg-Hanin test, statistical data processing was performed using Windows SPSS 11.5. and was carried out by means of standard methods. Results: Patients were divided on 3 subgroups depend on significant (р<0.05) Prl or C or their combination levels increasing. The presence of nonspecific signs of activation of the structures of the brain stem in patients with PA was established by EEG with significantly (р<0.05) higher frequency. The analysis of the psycho-emotional status of women showed a high level of personal and reactive anxiety. Conclusions: The revealed features of hormonal imbalance and psycho-emotional status in women with PA indicate the necessity of involving adjacent specialists - neurologists and psychotherapists for timely and adequate examination with the appointment of differentiated pathogenetically substantiated treatment.